Prognostic value of different lymph node staging methods for node-positive cardia gastric cancer: a register-based retrospective cohort study - Min Bao; Cheng Zhang; Xiao-Qing Wang (BMJ Open)
Objective To investigate the prognostic efficacy of lymph node ratio (LNR) and log odds of positive lymph nodes (LODDS) in node-positive cardia gastric adenocarcinoma (CGA).Design A registry-based retrospective cohort study.Setting Patients diagnosed with node-positive CGA in the Surveillance, Epidemiology, and End Results database from 2010 to 2015.Participants A total of 1038 patients were enrolled and randomly assigned (7:3) to the training set (n=723) or validating set (n=315).Primary outcome measure Cancer-specific survival (CSS).Results The baseline characteristics of the training and validation sets were similar. Based on the optimal cut-off values, LNR was classified into low (<0.09), medium (0.09~0.33) and high (>0.33) groups; LODDS was also classified into low (<−2.09), medium (−2.09~−0.65) and high (>−0.65) groups. CSS was significantly different across LNR and LODDS subgroups. The Harrell concordance index of the N stage was lower than that of the LNR or LODDS. The Akaike information criterion of the N stage was higher than that of the LNR or LODDS. Independent predictors included race, T stage, M stage and LNR (or LODDS), and they were incorporated into nomograms for 1-year, 2-year and 5-year CSS prediction. Calibration plots showed satisfactory results for internal and external validity of the nomogram.Conclusions LNR and LODDS staging methods have better prognostic efficacy than the traditional N staging method in CGA with node metastasis. Moreover, the two values are promising substitutes for N staging in nomogram development when other independent prognostic factors are incorporated.